2004
DOI: 10.1063/1.1769598
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substrate-induced strain on the structural, electrical, and optical properties of polycrystalline ZnO thin films

Abstract: The effect of substrate-induced strain in polycrystalline ZnO thin films on different substrate, e.g., GaN epilayer, sapphire (0001), quartz glass, Si(111)∕SiO2, and glass deposited by sol-gel process, has been investigated by x-ray diffraction, scanning electron microscope, electrical resistivity, and photoluminescence measurements. A strong dependence of orientation, crystallite size, and electrical resistivity upon the substrate-induced strain along the c axis has been found. The results of structural and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
189
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 456 publications
(210 citation statements)
references
References 16 publications
19
189
2
Order By: Relevance
“…18 Moreover, it can be observed that the (002) diffraction peak shifted from low angle degree (34.04 • ) to high angle degree (34.16 • ) as shown in the XRD patterns, indicating the internal stress state of the multilayer films changed while inserting a NiFe layer into ZnO. According to previous reports, 19,20 the in-plane biaxial stress in ZnO can be obtained from the following equation: where c and c 0 are the c-axis lattice constant evaluated from Bragg's law (2dsinθ = nλ) and the c-axis lattice constant for strain free bulk ZnO, respectively. The parameter σ is the residual in-plane biaxial stress calculated from the out-of-plane stress.…”
Section: Resultsmentioning
confidence: 74%
“…18 Moreover, it can be observed that the (002) diffraction peak shifted from low angle degree (34.04 • ) to high angle degree (34.16 • ) as shown in the XRD patterns, indicating the internal stress state of the multilayer films changed while inserting a NiFe layer into ZnO. According to previous reports, 19,20 the in-plane biaxial stress in ZnO can be obtained from the following equation: where c and c 0 are the c-axis lattice constant evaluated from Bragg's law (2dsinθ = nλ) and the c-axis lattice constant for strain free bulk ZnO, respectively. The parameter σ is the residual in-plane biaxial stress calculated from the out-of-plane stress.…”
Section: Resultsmentioning
confidence: 74%
“…The values of strain along the c-axis (ɛ zz ) are determined by using the following formula (Ghosh et al, 2004):…”
Section: Resultsmentioning
confidence: 99%
“…Strain can significantly modify the electronic band structures of a material [1][2][3], thus it can have strong effects on the structural, electrical and optical properties of the material [4][5][6]. Because of this, it has been extensive studied both theoretically and experimentally in the past decades and has often been used in designing electronic devices to enhance the device performance.…”
Section: Unusual Nonlinear Strain Dependence Of Valance-band Splittinmentioning
confidence: 99%
“…Because of this, it has been extensive studied both theoretically and experimentally in the past decades and has often been used in designing electronic devices to enhance the device performance. There are many different ways to apply strain, e.g., by applying external stress, having lattice and/or crystal structure mismatch between the epi-film and substrate [4] or between the layers in a heterostructure superlattice [7], or having reconstructions on a polar surface [8].…”
Section: Unusual Nonlinear Strain Dependence Of Valance-band Splittinmentioning
confidence: 99%